Technological readiness and business performance: the mediating effect of social media marketing - Bin-Obaidellah, Sabri Shaker Ashoor; Mokhtar, Noor Fadhiha; Mokhlis, Safiek; Awi, Nur Aishah (International Journal of Advances in Applied Sciences, 2025)
Understanding employee readiness towards adopting online marketing platforms is paramount in today’s digital economy, as it directly influences the effectiveness and competitiveness of businesses. This study investigates the relationship between employee technological readiness (ETR) and the business performance of micro and small enterprises (MSEs) in developing economies, focusing on data from Yemen. Drawing on the resource-based view theory, the study examined how adopting social media marketing (SMM) mediates this relationship. Data was collected from 362 managers/owners of MSEs in Yemen. The relationship between ETR, SMM, and business performance was examined using partial least squares structural equation modeling. The results show that ETR significantly influences SMM adoption, which impacts the business performance of MSEs. In addition, the study reveals that the relationship between ETR and business performance is partially mediated by SMM adoption. This finding highlights the critical role of employees’ readiness for technological advancements in facilitating effective SMM adoption, thereby contributing to the sustainability and success of MSEs.